The Edinburgh companion to Liz Lochhead - Varty, Anne (Edinburgh companions to Scottish literature., 2013)
Explores the significance of Liz Lochhead's work for the twenty-first century. The first contemporary critical investigation since Liz Lochhead's appointment as Scotland's second Scots Makar, this Companion examines her poetry, theatre, visual and performing arts, and broadcast media. It also discusses her theatre for children and young people, her translations for the stage as well as translations of her texts into foreign languages and cultures. Several poets offer commentaries on the influence of Liz Lochhead on their own practice while academic critics from America, Europe, England and Scotland offer new critical readings inspired by feminism, post-colonialism and cultural history. The volume addresses all of Lochhead's major outputs, from new appraisal of early work such as Dreaming Frankenstein and Blood and Ice to evaluations of her more recent works and collections such as The Colour of Black and White and Perfect Days. Key Features. : * Critical perspectives on Lochhead's established work and most recent interventions. * Situates Lochhead at the forefront of developing Scottish culture in a global context * Provides a bibliography of Lochhead's works and a select bibliography of criticism Keywords. : Liz Lochhead, Scottish Poetry, Scottish Theatre, Women's Writing, Dreaming Frankenstein, National Makar